'Write every day!': a mantra dismantled. Issue 4 (1st October 2016) - Sword, Helen
Abstract: Numerous books, blogs, and articles on research productivity exhort academics to 'write every day' even during the busiest of teaching times. Ironically, however, this research-boosting advice hangs from a perilously thin research thread. This article scrutinises the key findings of Robert Boice, whose pioneering studies of 'professors as writers' in the 1980s and 1990s are still widely cited today, and offers new empirical evidence to suggest that the writing practices of successful academics are in fact far more varied and individualistic than has generally been acknowledged in the literature.